Ministry of Trade And Industry Decree No. 415 Of The Year 2010 Concerning The Entities And Companies Granting Or Obtaining The ISO Certificates = وزارة التجارة والصناعة قرار رقم 415 لسنة 2010 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.